Parasitic predator preys on pink mealybugs - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1996)
The island of Grenada has suffered rapidly mounting levels of damage to its agricultural and horticultural production since the arrival of the pink mealybug (PMB) in 1993. The pest, Maconellicoccus hirsutus, is found in many other parts of the...